Financial Management Of The Turnover Of Micro, Small And Medium Enterprises (MSMEs) - Sinaga, Mahaitin H; Tarigan, Wico Jontarudi; Purba, Djuli Sjafei (Jurnal Ekuilnomi, 2024)
This study aims to examine the influence of financial management on the turnover of micro, small and medium enterprises (MSMEs). This study uses a quantitative method, with data collection techniques through questionnaires, observations, and interviews. The study population includes 113 MSME owners in Suka Mulia Sari Village, with a sample of 54 people determined using the Slovin formula. The sampling technique used is convenience sampling. The data testing in this study includes validity test, reality test, analysis prerequisite test, multiple linear regression analysis, Pearson product moment correlation and hypothesis proof using the help of SPSS Version 25. The result of this study is that there is no influence of financial management variables on MSME Turnover in Suka Mulia Sari Village with a significance value of 0.414 > 0.005 and tcount < ttable (0.824 < 1.675) meaning that there is no positive and significant influence of partial financial management variables on MSME Turnover). The results of the Pearson product moment correlation test showed a correlation coefficient value of 0.114. Because the value is close to 0, the relationship between financial management and MSME Turnover does not exist or there is no correlation